Pengaruh Output Daerah, Penerimaan Transfer Dan Desentralisasi Fiskal Terhadap Penerimaan Asli Daerah ( Pad ) Kota Pekanbaru - Syafril Basri (Jurnal Ekonomi, 2009)
Arm of this study are to identify influence regional output, transfer receive, and fiscal decentralizationon local own revenue of Pekanbaru City. Data used in this study are secondary data collected fromBoard of Statistic Center, Board of Regional Development Planning, and other department inPekanbaru. Main of analysis method is multiple linear regression. Variation of local own revenueinfluenced by variation of regional output, transfer receive, and fiscal desentralization are 99,2percent, and 0,8 percent influenced by others variabel. The rise regional output will increase localown revenue at confidence interval 99 percent. Meanwhile rising in transfer receive ratio willdecreasing local own revenue at confidence interval 99 percent.Implementation fiscaldecentralization in Pekanbaru City give rise of local own revenue at convidence interval 95 percent.